2017
DOI: 10.1542/peds.2017-0297
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences Among Hispanic Children in Immigrant Families Versus US-Native Families

Abstract: Children in immigrant families had significantly lower odds of ACE exposure despite higher prevalence of poverty. This may not reflect a true health advantage in this population. There may be unmeasured factors that buffer children in immigrant families from ACE exposure, or ACE questions may not capture the adverse experiences specific to immigrant families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 44 publications
(26 reference statements)
2
43
2
Order By: Relevance
“…Also of note was that Asian children in our clinic sample had the lowest burden of ACE. This compares well with Caballero et al ’s study using The National Survey of Children’s Health from the USA, which also found children in immigrant families to have significantly lower odds of ACE exposure despite higher prevalence of poverty 31. This information is important for planning effective service delivery, including adequate access and resources for children at risk of ACE.…”
Section: Discussionsupporting
confidence: 83%
“…Also of note was that Asian children in our clinic sample had the lowest burden of ACE. This compares well with Caballero et al ’s study using The National Survey of Children’s Health from the USA, which also found children in immigrant families to have significantly lower odds of ACE exposure despite higher prevalence of poverty 31. This information is important for planning effective service delivery, including adequate access and resources for children at risk of ACE.…”
Section: Discussionsupporting
confidence: 83%
“…The nding may re ect diversity of the Latinx caregivers in our study, where 64% are foreign-born, of whom 50% report immigration from Mexico and 45% from Central America. Several studies point to lower ACEs reported among foreign-born Latinx families compared with U.S.-born (27,28). There are also results that indicate that ACE assessments with Latinx families insu ciently capture Latinx experiences (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies point to lower ACEs reported among foreign-born Latinx families compared with U.S.-born (27,28). There are also results that indicate that ACE assessments with Latinx families insu ciently capture Latinx experiences (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, children of foreign-born parents report experiencing fewer types of early life adversity relative to children of US-born parents in the National Survey of Children's Health. 21,24 In addition, as reported in the 2011-2014 Behavioral Risk Factor Surveillance System, childhood adversities are disproportionately high among individuals identifying as a sexual minority. 9 Despite these reports of disparities in early life adversity exposure, there has been limited research to understand the variation in the associations between early life adversity and CVD risk across vulnerable populations, and even fewer prevention or treatment studies focused on these concerns.…”
Section: Disparities In Early Life Adversity and Cvd Riskmentioning
confidence: 99%